Answer:
The amount needed to pay off the loan after 4 years is $70,192
Step-by-step explanation:
When interest is compounded annually, total amount A after t years is given by:
![A = P(1 + r)^{t}](https://tex.z-dn.net/?f=A%20%3D%20P%281%20%2B%20r%29%5E%7Bt%7D)
where P is the initial amount (principal), r is the rate and t is time in years.
From the question:
P = $60,000
r = 4% = 0.04
t = 4
![A = 60000(1 + 0.04)^{4} \\A = 60000(1.04)^{4}\\A = 60000 * 1.16985856\\A = 70191.5136\\A = 70192](https://tex.z-dn.net/?f=A%20%3D%2060000%281%20%2B%200.04%29%5E%7B4%7D%20%5C%5CA%20%3D%2060000%281.04%29%5E%7B4%7D%5C%5CA%20%3D%2060000%20%2A%201.16985856%5C%5CA%20%3D%2070191.5136%5C%5CA%20%3D%2070192)
The amount needed to pay off the loan after 4 years is $70,192
If we divide the amount by four, we will get the amount that is paid yearly (70192/4 = 17548). $17,548 is paid yearly.
Answer:
$20.60
Step-by-step explanation:
25.75x20%=5.15
25.75-5.15=20.60
Answer:
.
Step-by-step explanation:
We have been an division problem:
.
We will simplify our division problem using rules of exponents.
Using product rule of exponents
we can write:
![45^{45}=(9*5)^{45}=9^{45}*5^{45}](https://tex.z-dn.net/?f=45%5E%7B45%7D%3D%289%2A5%29%5E%7B45%7D%3D9%5E%7B45%7D%2A5%5E%7B45%7D)
![75^{30}=(15*5)^{30}=15^{30}*5^{30}](https://tex.z-dn.net/?f=75%5E%7B30%7D%3D%2815%2A5%29%5E%7B30%7D%3D15%5E%7B30%7D%2A5%5E%7B30%7D)
Substituting these values in our division problem we will get,
![\frac{9^{45}*5^{45}*3^{15}*5^{15}}{15^{30}*5^{30}}](https://tex.z-dn.net/?f=%5Cfrac%7B9%5E%7B45%7D%2A5%5E%7B45%7D%2A3%5E%7B15%7D%2A5%5E%7B15%7D%7D%7B15%5E%7B30%7D%2A5%5E%7B30%7D%7D)
Using power rule of exponents
we will get,
![\frac{9^{45}*5^{(45+15)}*3^{15}}{15^{30}*5^{30}}](https://tex.z-dn.net/?f=%5Cfrac%7B9%5E%7B45%7D%2A5%5E%7B%2845%2B15%29%7D%2A3%5E%7B15%7D%7D%7B15%5E%7B30%7D%2A5%5E%7B30%7D%7D)
![\frac{9^{45}*5^{60}*3^{15}}{15^{30}*5^{30}}](https://tex.z-dn.net/?f=%5Cfrac%7B9%5E%7B45%7D%2A5%5E%7B60%7D%2A3%5E%7B15%7D%7D%7B15%5E%7B30%7D%2A5%5E%7B30%7D%7D)
Using product rule of exponents
we will get,
![\frac{(3*3)^{45}*5^{60}*3^{15}}{(3*5)^{30}*5^{30}}](https://tex.z-dn.net/?f=%5Cfrac%7B%283%2A3%29%5E%7B45%7D%2A5%5E%7B60%7D%2A3%5E%7B15%7D%7D%7B%283%2A5%29%5E%7B30%7D%2A5%5E%7B30%7D%7D)
![\frac{3^{45}*3^{45}*5^{60}*3^{15}}{3^{30}*5^{30}*5^{30}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E%7B45%7D%2A3%5E%7B45%7D%2A5%5E%7B60%7D%2A3%5E%7B15%7D%7D%7B3%5E%7B30%7D%2A5%5E%7B30%7D%2A5%5E%7B30%7D%7D)
Using power rule of exponents
we will get,
![\frac{3^{(45+45+15)}*5^{60}}{3^{30}*5^{(30+30)}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E%7B%2845%2B45%2B15%29%7D%2A5%5E%7B60%7D%7D%7B3%5E%7B30%7D%2A5%5E%7B%2830%2B30%29%7D%7D)
![\frac{3^{105}*5^{60}}{3^{30}*5^{60}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E%7B105%7D%2A5%5E%7B60%7D%7D%7B3%5E%7B30%7D%2A5%5E%7B60%7D%7D)
![\frac{3^{105}}{3^{30}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E%7B105%7D%7D%7B3%5E%7B30%7D%7D)
Using quotient rule of exponent
we will get,
![\frac{3^{105}}{3^{30}}=3^{105-30}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E%7B105%7D%7D%7B3%5E%7B30%7D%7D%3D3%5E%7B105-30%7D)
![3^{105-30}=3^{75}](https://tex.z-dn.net/?f=3%5E%7B105-30%7D%3D3%5E%7B75%7D)
Therefore, our resulting quotient will be
.
Answer:
North east
Step-by-step explanation: